KONSEP KEPEMIMPINAN PEREMPUAN DALAM PANDANGAN ABDUR RAUF AS-SINGKILI - Razali, Maulana; Mansur, Muhammad; Hanif, Hanif; Al-Fairusy, Muhajir (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
Tarjuman Al-Mustafid is the first book of Tafsir 30 juz in the archipelago, which became a guide for the people of Aceh at that time. The Kingdom of Aceh Darussalam was founded in 1496-1903, ruling for 407 years. Of the royal leaders (sultans) there were four sultanates who led successively, and Abdur Rauf As-Singkili as Qadhi malik al'amin who was appointed by the first sultanah Sri Ratu Tajul Alam Safiatuddin johan sovereign in 1661. Abdur Rauf was appointed and give responsibility as Qadhi, advisor, and religious interpreter of the kingdom. What are his thoughts in his commentary book Tarjuman Al-Mustafid, is the interpretation of the verse about leadership influenced by royal politics? The author is interested in writing this theme to find out the interpretation of the verses of the Koran about leadership according to Abdur Rauf As-Singkili, and to know the concept of women's leadership according to Abdur Rauf As-Singkili. The results of the study prove that Abdurrauf's interpretation of the leader in QS. An-Nisa' verses: 19, 20, 34 and 58, are not influenced by royal politics. Abdurrauf does not interpret that a woman can be a leader. However, his activities in the kingdom with his position as Kadhi Malik Al 'Adil, Abdurrauf has the responsibility as an advisor to the Sultanah as well as the application of law in the Kingdom of Aceh Darussalam. he allowed a woman to be the leader. This can be seen in several events and his work. Abdurrauf issued a fatwa to challenge the campaign of the embodiments who wished to overthrow Sultanah's position, and in his book Miraatul Thulab in his preamble there is a commendation of Sultanah Safiatuddin,